2018
DOI: 10.1021/acs.jpcc.8b10276
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doping Chemical Behavior of Graphene Materials with Assistance of Defluorination

Abstract: Heteroatom-doping reactions are essential to achieve advanced graphene-based materials for energy and biological areas. Unfortunately, considerably less is known regarding the detailed reaction pathways up to now. Here, we focus on investigating the nitrogen (N) doping process of fluorinated graphene (FG) under the assistance of defluorination based on modified in situ Fourier transform infrared spectroscopy. It was demonstrated FG possesses a higher and more effective reactivity with ammonia in comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…However, although a structurally well-defined graphene derivative was used as a substrate, allowing homogeneous doping, the pathway relied on established high temperature routes and yielded only low N content. It was also demonstrated that FG can undergo direct N-doping by ammonia gas which occurs simultaneously with defluorination at temperatures between 200 and 400 °C. , Density functional theory (DFT) calculations have revealed that the first reaction step involves nucleophilic substitution of fluorine atoms by amino groups, which can then undergo deprotonation and cyclization into aziridinic configurations. These could potentially be transformed into either pyridinic or graphitic N in the honeycomb carbon lattice.…”
Section: Introductionmentioning
confidence: 99%
“…However, although a structurally well-defined graphene derivative was used as a substrate, allowing homogeneous doping, the pathway relied on established high temperature routes and yielded only low N content. It was also demonstrated that FG can undergo direct N-doping by ammonia gas which occurs simultaneously with defluorination at temperatures between 200 and 400 °C. , Density functional theory (DFT) calculations have revealed that the first reaction step involves nucleophilic substitution of fluorine atoms by amino groups, which can then undergo deprotonation and cyclization into aziridinic configurations. These could potentially be transformed into either pyridinic or graphitic N in the honeycomb carbon lattice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned application fields, the application of FG in other aspects have also been preliminarily reported by investigators. [170,[218][219][220][221][222][223][224][225][226][227][228][229][230] Zhao et al's study indicated that FG with single-sided fluorination could be used as the metal-free electrocatalyst in ORR reactions. Through simulations, single-sided fluorinated graphene had a high spin density, which enhanced the adsorption of O 2 and promoted the 4e − reaction process with an excellent electrocatalytic activity.…”
Section: Other Applicationsmentioning
confidence: 99%
“…In addition to the aforementioned application fields, the application of FG in other aspects have also been preliminarily reported by investigators. [ 170,218–230 ] Zhao et al. 's study indicated that FG with single‐sided fluorination could be used as the metal‐free electrocatalyst in ORR reactions.…”
Section: Applications Of Fgmentioning
confidence: 99%
“…CNTs are indeed a new class of material useful for environmental applications because of their cylindrical hollow structure, large surface area, high length to radius ratio, and hydrophobic wall and surface that can be easily modified [13].GO is one oxidized analog of graphene, recognized as the promising intermediate for obtaining the latter in large scale [14], since Brodie centuries ago first reported about the oxidation of graphite [15]. Three decades earlier, one atom-thin single layer of graphite was officially defined with the term graphene [16], structurally comprising sp 2 hybridized carbon atoms arranged in a honeycomb lattice, characterized by promising properties in terms of mechanical, electrical, and other [17][18][19]. Despite well-known properties, GO remains limited success in practical applications, mainly due to the difficulties in large-scale production of desired highlyorganized structure [20].…”
Section: Introductionmentioning
confidence: 99%